2022
DOI: 10.3389/fpubh.2022.927658
|View full text |Cite
|
Sign up to set email alerts
|

Area Deprivation and COVID-19 Incidence and Mortality in Bavaria, Germany: A Bayesian Geographical Analysis

Abstract: BackgroundArea deprivation has been shown to be associated with various adverse health outcomes including communicable as well as non-communicable diseases. Our objective was to assess potential associations between area deprivation and COVID-19 standardized incidence and mortality ratios in Bavaria over a period of nearly 2 years. Bavaria is the federal state with the highest infection dynamics in Germany and demographically comparable to several other European countries.MethodsIn this retrospective, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
3
0
3
Order By: Relevance
“…Conversely, findings from a study in Bavaria, Germany showed that increasing vaccination coverage appeared to balance incidence and mortality rates between the most and least deprived districts [ 19 ]. Two of several factors which could explain these temporal pattern differences are inter-study heterogeneity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, findings from a study in Bavaria, Germany showed that increasing vaccination coverage appeared to balance incidence and mortality rates between the most and least deprived districts [ 19 ]. Two of several factors which could explain these temporal pattern differences are inter-study heterogeneity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque la COVID-19 ha afectado a países de ingresos dispares, existe evidencia para demostrar que los determinantes sociales y económicos tienen un impacto en la incidencia, la gravedad y la mortalidad asociada 21 , 22 , 23 , 24 , 25 , 26 , 27 . La mayoría de los estudios sobre la COVID-19 y los diferentes niveles de privación se han centrado en averiguar si había diferencias en las tasas de mortalidad y de hospitalización según los niveles de privación 21 , 22 , 23 , 25 , 28 , 29 , 30 ; otros se han centrado en su relación con la tasa de infección 21 , 23 , 24 , 25 , 27 . En todos ellos se ha encontrado que los colectivos más desfavorecidos, con mayor nivel de privación, han tenido tasas más altas de infección, de mortalidad y de ingreso en comparación con los colectivos con unas tasas de privación más bajas.…”
Section: Discussionunclassified
“…En algunos casos, los estudios también han encontrado discrepancias entre diferentes tiempos de la pandemia, con resultados dispares por estudios y olas 21 , 25 . En nuestro caso, al igual que en el estudio de Manz et al 25 , las mayores desigualdades se observaron durante el primer y el tercer periodos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The BIMD is a measure of relative deprivation which combines indicators in certain domains of deprivation to generate a comprehensive deprivation index ( 19 , 20 ). The index, last updated in 2015, consists of the following seven domains: income (weight: 25%), employment (25%), education (15%), district revenue (15%), social capital (10%), environment (5%), and security (5%) ( 19 , 21 ). High BIMD values indicate high deprivation (meaning low income, high unemployment, etc.)…”
Section: Methodsmentioning
confidence: 99%